The role of protein lactylation in brain health and disease: current advances and future directions - Mingrui Han; Wenfeng He; Wengen Zhu; Linjuan Guo (Cell Death Discovery)
Abstract Lactate, the end product of glycolysis, plays a crucial role in cellular signaling and metabolism. The discovery of lactylation, a novel post-translational modification, has uncovered the role of lactate in regulating diseases, especially in the brain. Lactylation connects genetic encoding with protein function, thereby influencing key biological processes. Increasing evidence supports lactate-mediated lactylation as a critical modulator in neurological disorders. This review offers an overview of lactate metabolism and lactylation, highlighting recent advances in understanding the regulatory enzymes of lactylation and their role in the central nervous system. We investigate the impact of lactylation on brain dysfunctions, including neurodegenerative diseases, cerebrovascular disorders, neuroinflammation, brain tumors, and psychiatric conditions. Moreover, we highlight the therapeutic potential of targeting lactylation in treating brain disorders and outline key research gaps and future directions needed to advance this promising field.